Edukasi dan Sosialisasi Pengelolaan Sampah Plastik pada KSM Srimenanti Jaya Sungailiat Bangka - Verry Andre Fabiani (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Plastic waste is a source of problems in landfills because of its large size and difficult to decompose. The high amount of plastic waste is caused by people's dependence on plastic which is also getting bigger. Based on the results of observations made in Sri Menanti Village, Sungailiat, Bangka Regency, information was obtained that plastic waste is one of the wastes that has not been properly optimized. Education is carried out in the form of assistance to KSM managers which emphasizes Government Regulation Number 81 of 2012 concerning the Implementation of Waste Infrastructure and Facilities in Handling Household Waste and Waste Similar to Household Waste. In addition to education, socialization is also given about the use of plastic waste into products that have economic value, one of which is ecobricks and handicrafts. The service activities were carried out well and received full support from KSM by following up on the results of the service through the manufacture of ecobricks and handicrafts from plastic waste in the future.